Tilt measurement using inclinometer based on redundant configuration of MEMS accelerometers. (27th March 2018) - Lu, Jiazhen; Liu, Xuecong; Zhang, Hao
Abstract: Inclinometers are widely used in tilt measurement and their required accuracy is becoming ever higher. Most existing methods can effectively work only when the tilt is less than 60°, and the accuracy still can be improved. A redundant configuration of micro-electro mechanical system accelerometers is proposed in this paper and a least squares method and data processing normalization are used. A rigorous mathematical derivation is given. Simulation and experiment are used to verify its feasibility. The results of a Monte Carlo simulation, repeated 3000 times, and turntable reference experiments have shown that the tilt measure range can be expanded to 0°–90° by this method and that the measurement accuracy of θ can be improved by more than 10 times and the measurement accuracy of γ can be also improved effectively. The proposed method is proved to be effective and significant in practical application.